The Vortex Of Corruption In The Midst Of Local Government And Its Prevention: The Destruction Of Integrity Values - Muhammad Buchori Muslim (Socio Legal and Islamic Law, 2022)
Corruption in recent years has been fussed with many being involved in corruption cases. This corruption then results in losses suffered by the public, such as poverty and social inequality etc. From 2004 to February 2021, a total of 126 regional heads have been designated by the KPK as corruption suspects. . Corruption cases that occur in the government, especially local governments, cannot be separated from the weak prevention function from within. As for based on data from the KPK, the highest number of corruption crimes from 2004 to 2019 was in local government agencies (provincial and regency / city) as many as 500 cases out of a total of 1032 cases. Efforts to fight or eradicate corruption are not enough to arrest and throw corruptors in jail, because opportunities for corruption are wide in front of would-be corruptors. That is why it is necessary to instill good values of Integrity and make efforts to make efforts to cultivate.  Keywords : Corruption, Local Government, Integrity Values, Prevention